Disclosure of information under competition: An experimental study - Jesal Sheth (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
The theory of voluntary disclosure of information posits that market forces lead senders to disclose information through a process of unravelling. This prediction requires that receivers hold correct beliefs and, in equilibrium, make adverse inferences about non-disclosed information. Previous research finds that receivers do not sufficiently infer non-disclosure as bad news, leading to the failure of complete unravelling. This paper experimentally examines whether competition between senders when receivers strongly prefer disclosed over nondisclosed information increases unravelling. We further examine whether receivers' naivety about non-disclosed information decreases with competition between senders. We find that complete unravelling fails to occur without competition. However, with competition, there is significantly higher unravelling such that it increases receivers' overall welfare. Interestingly, receivers' welfare increases despite no significant difference in their guesses or beliefs about non-disclosed information relative to the treatment without competition. We conclude that competition between senders positively affects disclosure of information and receivers' welfare.
Keywords: C92; D82; D83; L15; 330; Competition; experiment; disclosure; verifiable information; conflict of interest